Memory Functioning in Obsessive-Compulsive Disorder - M. Abbruzzese; L. Bellodi; S. Ferri; S. Scarone (Behavioural Neurology)
A number of studies have reported neuropsychological deficits in obsessive-compulsive disorder (OCD). These have mainly implicated frontal or temporal dysfunction. In this study, we compared the performances of OCD patients and normal subjects using a factorial interpretation of the Wechsler Memory Scale. Our results do not demonstrate significant memory impairment in OCD patients but point to the possibility of frontal lobe dysfunction as a factor in the pathophysiology of OCD.